Philosophical Overview of the Relationship between Budget Users and the State General Treasurer in the Management of Financial State (Indonesia Experience) - Achmat Subekan; Azwar Iskandar (Budapest International Research and Critics University, 2021)
Legislation on state financial management is a legal form of state financial management that has a rationale. Understanding the philosophical basis of the rationale will provide strengthening of understanding of the relevant laws and regulations and authority and responsibilities to the Budget User and the State General Treasurer. This study aims to find out the rationale used in state financial management, especially related to the authority and division of responsibility between the Budget User and the State General Treasurer in the state financial management. This research uses descriptive qualitative method with library research and cotent analysis technique with normative juridical approach . The results found that the Budget User and the State General Treasurer had an equal standing under the President. Both are packaged in check and balance relationships to protect the country's finances from arbitrary actions by certain parties. Philosophically, the Budget User is a party that